Hubungan antara Trust dan Kepribadian Agreeableness dengan Intensi Berbagi Pengetahuan pada karyawan perusahaan berbasis Knowledge Management di PT. Pertamina Balikpapan - ., Helena Mariani (MOTIVASI, 2014)
ABSTRACTThis research aims to determine whether there are significant relationshipsbetween trust and agreeableness personality with knowledge sharing intention. Theindependent variables of this research are trust and agreeableness personality,meanwhile the dependent variable is knowledge sharing intention. The hypotheses ofthis research are; (1) there is a relationship between trust and knowledge sharingintention, (2) there is a relationship between agreeableness personality andknowledge sharing intention and (3) simultaneously, there are relationships betweentrust and agreeableness personality with knowledge sharing intention.This research was addressed to employees on Knowledge Management basedcompany and surveyed 101 employees of PT. Pertamina Balikpapan especially in theMarketing Unit of Region VI. This research used the random sampling by Slovinformula.Data analysis technique used multiple regression analysis. The results showedthat there were positive and significant relationship between trust and knowledgesharing intention with beta = 0.238, R2 = 0.482, t = 4.860 and p = 0.000. Therewas a relationship between agreeableness personality with knowledge sharingintention with the value of beta = 0.759, t = 15.509, R2 = 0.814 and p = 0.000.Then there were significant relationships between trust and agreeablenesspersonality with knowledge sharing intention, with F = 278.033, R2 = 0.847, and p= 0.000 .